The management of quality in distance-learning education at UiTM Dungun, Terengganu. An analysis of the SERVQUAL dimensions - Zakaria, Zainuddin; Amirrudin, Faizatul Akmam; Awang, Moktar (2004)
There is mounting pressure from customers of higher education to close the widening gap between their expectations of institutional performance and their perceived quality of the actual service performance. In view of this development, the researchers engaged in a study of evaluating the perceptions of the E-PJJ (Pengajian Jarak Jauh) students towards services offered by the Distance Learning Programme at Universiti Teknologi MARA (UiTM), Dungun campus, Terengganu. The researchers conducted the research based on the SERVQUAL model proposed by Parasuraman et al. (1988) that suggests that a service quality consists of five dimensions, namely Tangibility, Reliability, Responsiveness, Assurance and Empathy. Based on this model, the researchers evaluated the gap between the expectations and the perceived quality of the students towards the five service quality dimensions hoping to discover which service dimensions that may require improvement. A sample of 57 students was chosen from a total population of 77 students. Respondents were given questionnaires requiring them to evaluate their expectations with regard to services provided by UiTM and their perceptions of the actual service experience. The researchers discovered that even though there are gaps between the expectations of the students with their actual experience of receiving the service (perceptions) on all five-service dimensions, the majority show a high degree of satisfaction towards the service provided by the Distance Learning Programme at UiTM Dungun.